Resepsi Remaja di Jakarta Mengenai Perselingkuhan Orangtua pada Program Reality Show “Harta Tahta Wanita” di Trans TV - Pamela Yosepa; Dyah Kusumawati (UNIVERSITAS KALBIS, 2022)
This study aims to determine the meaning adolescents in Jakarta in interpreting parents infidelity in the reality show “Harta Tahta Wanita”. This study uses qualitative approach, constructivist paradigm, and descriptive research types. Researchers use audience reception analysis with Stuart Hall’s encoding-decoding theory which divides audiences into three positions: dominant hegemony, negotiation and opposition. The data collection technique used was in-depth interviews. The results of this study show that the negotiation position is the most dominant, because the informants had personal experiences regarding parental infedelity. Meanwhile, the positions of dominant hegemony and the position opposition doesnt dominate in every informations. This classification aims to make researcher know the receptions of adolescent in Jakarta regarding parental infedelity by Harta Tahta Wanita.